MANAJEMEN KELAS DALAM MENINGKATKAN PROSES PEMBELAJARAN - Muldiyana Nugraha (Tarbawi, 2018)
The purpose of this research to describe the planning of classroom management, the implementation of classroom management, supporting and hibiting factors of classroom management to increase learning process, and than the strategy to increase learning process. The research methodology is descriptive qualitative method. The result showed that the planning of classroom management do with prepared and arrange set of equipment and instrumen of study. The implementation of classroom management in the study appled some classroom management principles and some approaches. The supporting and inhibiting factors are physical environment, social emotional and organization condition. The strategy was students condition for already study in the class, learn to concentration, using the right method and variation, interaction in educatif and communicative, and than the students were using media with the teaching was. Keywords. Classroom Management, Learning Process